1989
DOI: 10.1016/0735-1097(89)90181-2
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial beta-adrenoceptor changes in heart failure: concomitant reduction in beta,- and beta2-adrenoceptor function related to the degree of heart failure in patients with mitral valve disease

Abstract: In patients suffering from end-stage congestive cardiomyopathy, cardiac beta 1-adrenoceptor function is markedly reduced, whereas cardiac beta 2-adrenoceptor function is nearly normal. To determine whether beta 1-adrenoceptor function is impaired in heart failure selectively, beta 1- and beta 2-adrenoceptor density and functional responsiveness in the right and left atria and the left papillary muscles from patients with mitral valve disease (functional class III to IV) were studied. In all three tissues conco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(40 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…Studies in human hearts have shown a reduction in the number of 3-adrenergic receptors ( 12-17), particularly of the f3I subtype ( 1 1, 12, 17), from the left ventricle of failing hearts. Recently, considerable attention has been directed to the pacing-induced heart failure model (8,9), in that it exhibits many features common to human heart failure, e.g., the changes in 0-adrenergic receptor signaling in this model approximate those in human studies (12)(13)(14)(15)(16)(17). The majority of these studies as well as all of the studies using human myocardium have focused on later stages in the disease process, after congestive heart failure has been established for some time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in human hearts have shown a reduction in the number of 3-adrenergic receptors ( 12-17), particularly of the f3I subtype ( 1 1, 12, 17), from the left ventricle of failing hearts. Recently, considerable attention has been directed to the pacing-induced heart failure model (8,9), in that it exhibits many features common to human heart failure, e.g., the changes in 0-adrenergic receptor signaling in this model approximate those in human studies (12)(13)(14)(15)(16)(17). The majority of these studies as well as all of the studies using human myocardium have focused on later stages in the disease process, after congestive heart failure has been established for some time.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial /-adrenergic receptor density has been demonstrated to be increased (5, 6), unchanged (7), or decreased (8)(9)(10)(11) in experimental animals with heart failure. and others (15)(16)(17) have consistently shown a reduction in the number of 3-adrenergic receptors, particularly of the A, subtype ( 1 1, 12, 17), in the left ventricle of failing human hearts. Most prior studies have exam-ined the advanced or terminal stages of heart failure, or examined a single component of the d receptor-GTP-stimulatory protein (Gj) '-adenylyl cyclase pathway, leaving an incomplete picture as to the development of the abnormalities in 3-adrenergic signal transduction.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Bernardi et al,15 an increase in the PEP/LVET ratio was observed in both pate in the cardiac contractile responses. 37,38 The structure of the b-adrenergic receptor has recently been elucidated. alcoholic and nonalcoholic cirrhotic patients, and no significant difference in the magnitude of the cardiac abnormalities The cardiac b-adrenoceptor is, like other G-protein (guanosine triphosphate-binding protein)-coupled receptors, comwas found between the two groups.…”
Section: Cardiac Histology In Cirrhosismentioning
confidence: 99%
“…[3][4][5][6][7][8] The response of failing myocytes to increasing beating rates is also abnormal. 9 In the normal heart, contraction rate and magnitude increase with beating rate (often termed a positive force-frequency relationship), whereas in the failing myocardium, contractions decrease over the same range of frequencies.…”
Section: See P 2297mentioning
confidence: 99%